Characterisation of gluten‐free couscous produced with different legume flours by traditional method. (23rd January 2023) - Boudouira, Nassira; Yüksel, Ayşe Nur; Bayram, Mustafa; Benatallah, Leila; Zidoune, Mohammed Nasreddine
Summary: Couscous is a traditional cereal product usually prepared using semolina; however, couscous may be produced with different flours as well as gluten‐free flours. In this study, gluten‐free couscous was prepared by supplementing rice flour with flours of field bean, chickpea and lentil (90/10 or 70/30%, w/w). The objective of this study was to develop gluten‐free couscous and determine the quality, texture, microstructure and sensory properties, which these properties were used for characterisation. The results revealed that the gluten‐free couscous had low water absorption capacity, low swelling and cohesion and slightly high disintegration degree compared to the control couscous. Protein, lipid and ash contents were improved following the supplementation while lightness and hardness were negatively affected. Even though there was no gluten, the significant yield was obtained during production. Moreover, the quality, texture and sensory properties of gluten‐free couscous were close to those of the control couscous. Gluten‐free couscous production was successfully achieved for whom wants to consume gluten‐free products as a lifestyle. Abstract : Gluten‐free couscous samples were produced by the supplementation of rice flour with different legume flours (field bean, chickpea and lentil) by traditional method. Characterisation of couscous samples was made with varying experiments. The results revealed that the supplementation of rice flour with legumes provided higher nutritional value and yield, besides, it was possible to obtain technologically feasible gluten‐free couscous which had the similar results with semolina couscous.